An Assessment of Indigenous Beliefs and Practices of Alternative Medicine by Its Users in Nde Division, Cameroon - Ndeloa, Dremoh (European Scientific Journal, ESJ, 2024)
This study examines the role of indigenous beliefs and practices in shaping healthcare choices in Cameroon’s Nde Division, where alternative medicine is deeply rooted in cultural and spiritual traditions. A mixed-methods approach combining surveys and interviews revealed that 80% of participants believe in the efficacy of indigenous healing traditions, with 70% using alternative medicine due to cultural and spiritual beliefs. Economic, social, cultural, and individual factors influence the adoption of alternative healing methods, with users relying on natural remedies and spiritual practices passed down through generations. However, concerns around safety and efficacy highlight the need for education, regulation, and integration with conventional healthcare. This research underscores the importance of cultural sensitivity and inclusivity in healthcare delivery, emphasizing the need for healthcare providers to consider the cultural nuances and values of this community. By understanding the cultural and spiritual beliefs underlying patients’ choices, healthcare providers can promote more effective and respectful care.